Growing Miracle Fruit for Specialty Crop Production in Florida - Lynhe Demesyeux; Maria Brym; Alan H. Chambers (EDIS)
Miracle fruit is the botanical source of miraculin and an understudied tropical fruit species with potential as a natural, noncaloric sweetener. Miraculin changes the perception of sour (acidic) foods and beverages to sweet by temporarily modifying taste receptors on the tongue. This report provides background information on growing miracle fruit, information on miracle fruit yield, and research on miraculin content to commercial growers and those interested in gardening in southern Florida. Written by Lynhe Demesyeux, Maria Brym, and Alan H. Chambers, and published by the UF/IFAS Horticultural Sciences Department; 6 pp. https://edis.ifas.ufl.edu/hs1449